If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16k = -15k + -16 Reorder the terms: -16k = -16 + -15k Solving -16k = -16 + -15k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '15k' to each side of the equation. -16k + 15k = -16 + -15k + 15k Combine like terms: -16k + 15k = -1k -1k = -16 + -15k + 15k Combine like terms: -15k + 15k = 0 -1k = -16 + 0 -1k = -16 Divide each side by '-1'. k = 16 Simplifying k = 16
| -4n+5=13 | | -4+5=13 | | 8x/20x=9/20 | | 6x-6+x=4x+8 | | -9x+2.6+(-x)+(-12.8)= | | 2x+9-3x=12 | | z^2+16z+7=0 | | X+3y+3z=10 | | x/x^2=0 | | (Ab+b-c+6)+(3ab-b+c-6)= | | 8a-4(-5a-2)=24a | | 6u+8=21 | | 2y-24=26 | | 1/3s=-2 | | 10-2/5x=-3 | | 5e+6pd+5d-7ed+7= | | 10-2/5x=3 | | 1/2(13f/5 | | 4-1/2v=-4 | | 2.5+-3.5x=-32x+-48 | | 4-1/2v=4 | | 12+4pd-2p+6pd= | | -5w^3-4w^2=7w+16 | | 2.5+-3.5x=-32+-48 | | 8-5n=3.25 | | -3yx+2x+6y-4=0 | | 5x-9=54-4x | | 2x+3y+4x+5x+6x= | | 2x+2x-6=8 | | P+pq-q-p+3pq-3-q+7= | | 6m^2+23m+15=0 | | (-5r-4)(-r-6)= |